Impact Of Solar Radiation On High-Rise Built Form In Tropical Climate - Ahmad, M. Hamdan; Dilshan, Ramez Ossen; Chia, Sok Ling (2004)
This study investigates on the impacts of solar radiation towards high-rise building form, orientation and building envelope. High-rise building is exposed to overheating in the tropical climate or equatorial region. For a high-rise built form, vertical surface is most critically exposed to direct solar radiation. The computer program â€œEcotect v5.2â€? was applied to simulate the intensity and distribution pattern of cumulative incident solar radiation on vertical surfaces. The simulation results reveal that south orientation is the most critical part to be protected than others parts. By combining different passive solar design strategies - core position, recessing space and self-shading envelope - intensity of solar radiation striking on the high-rise built form can be reduced up to 40%.